The reliability of fire protection system case study of Aceh Besar district regency office. Issue 1 (September 2020) - Anwar, F; Aulia, T B; Afifuddin, M
Abstract: The Regency Office is a building where the central government is administered in an administrative area at the district level. According to the Pd-T-11-2005-C regulation on building fire safety inspections, in order to ensure the safety and comfort of the building, the value of building safety system reliability (VBSSR) should not be less than 80%. This study aims to evaluate the value of the reliability of the office building safety system and propose recommendations on the reliability conditions of the Building of Aceh Besar District Regency Office. This study uses qualitative methods through observation. Evaluation of the reliability of building safety systems and recommendations on building reliability conditions is carried out based on technical guidelines of the Pd-T-11-2005-C regulations. The objects of the observations are the completeness of the site, rescue devices, active protection systems, and passive protection systems. For data analysis, the researcher used the scoring analysis (weighting). The results showed that the reliability value of the safety system of the Building of Aceh Besar District Regency Office was 74.97%, and the reliability was at a sufficient level.